2020
DOI: 10.1186/s13244-019-0819-2
|View full text |Cite
|
Sign up to set email alerts
|

CEUS LI-RADS: a pictorial review

Abstract: Contrast-enhanced ultrasound (CEUS) greatly improved the diagnostic accuracy of US in the detection and characterization of focal liver lesions (FLLs), and it is suggested and often included in many international guidelines as an important diagnostic tool in the imaging work-up of cirrhotic patients at risk for developing hepatocellular carcinoma (HCC). In particular, CEUS Liver Imaging Reporting and Data System (LI-RADS) provides standardized terminology, interpretation, and reporting for the diagnosis of HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 67 publications
(78 reference statements)
0
48
0
Order By: Relevance
“…Nonetheless, their proposal was considered misleading by the ACR and consequently denied [110]. [59,111]. This table includes only CEUS pure blood pool agents (SonoVue, Luminity).…”
Section: Diagnostic Features Of Hepatocellular Carcinoma On Ceusmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, their proposal was considered misleading by the ACR and consequently denied [110]. [59,111]. This table includes only CEUS pure blood pool agents (SonoVue, Luminity).…”
Section: Diagnostic Features Of Hepatocellular Carcinoma On Ceusmentioning
confidence: 99%
“…Yang et al [98] reported no significant difference on the dynamic enhancement of HCC using CEUS in patients with or without cirrhosis. [59,111]. This table includes only CEUS pure blood pool agents (SonoVue, Luminity).…”
Section: Hcc Particularities In Nafld Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several international guidelines currently recommend CEUS as a useful imaging modality for the radiological work-up of HCC, such as the LI-RADS lexicon of the American College of Radiology[ 22 , 30 , 31 ].…”
Section: Contrast-enhanced Usmentioning
confidence: 99%
“…This algorithm accounts for size, arterial phase hyperenhancement and wash out phenomenon in later phases. Arterial phase hyperenhancement (APHE) of liver lesions is a major determining factor for the classification of HCC by CEUS 9 , 11 , 15 . APHE reflects the process of arterial angiogenesis which is a key component of HCC pathogenesis, where predominantly arterial rather than portal-venous blood supply is drawn by HCC 16 .…”
Section: Introductionmentioning
confidence: 99%